Morphology and taxonomy of deutonymphs of the genus Unionicola Haldeman, 1842 (Acari, Hydrachnidia, Unionicolidae) in Russia - Tuzovskij, Petr V.; Semenchenko, Ksenia A. (Zootaxa, 2015)
This study presents a detailed taxonomic review of water mite deutonymphs of the genus Unionicola Haldeman, 1842 (Hygrobatoidea: Unionicolidae) found in the fauna of Russia during the long-term survey period of 1979–2013. The review includes descriptions and illustrations of 14 Unionicola species found in this country: U. aculeata (Koenike, 1890), U. arcuata (Wolcott, 1898), U. bonzi (Claparède, 1869), U. hankoi Szalay, 1927, U. intermedia (Koenike, 1882), U. japonensis Viets, 1933, U. inusitata Koenike, 1914, U. tricuspis (Koenike, 1895), U. crassipes (Müller, 1776), U. gracilipalpis (Viets, 1908), U. markovensis Tuzovskij, 1990, U. minor (Soar, 1900), U. rossica Tuzovskij & Semenchenko, 2015, U. ypsilophora (Bonz, 1783). Key to all species based on deutonymphs is presented.